Between Job Demands and Work Engagement: Considering the Mediating Role of Work-Life Balance and Perceived Organizational Support - Alisa, Rezki Noor; Said, Laila Refiana (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study examines the effect of job demands on work engagement by considering the mediating roles of work-life balance and perceived organizational support (POS) among employees at the Audit Board of Indonesia (BPK) Representative Office in South Kalimantan Province. Using a quantitative approach and census method, 125 respondents participated in this survey. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) via SmartPLS. The findings reveal that job demands, POS, and work-life balance all have a significant effect on work engagement. However, work-life balance and POS do not mediate the relationship between job demands and work engagement. These results suggest that employees respond directly to job demands in a highly professional and demanding work environment, such as BPK, by enhancing their engagement without relying heavily on work-life balance or organizational support.